PREVENTIVE PROMOTION “STOP TRASH” OF SNAKE AND LADDER GAME IN IMPROVING STUDENT KNOWLEDGE AND ATTITUDE - Fitriyah, Sukhriyatun; Rahmawati, Ade (JURNAL KESEHATAN INDRA HUSADA, 2020)
The high number of waste generation in Indonesia shows the minmize of public concern in managing waste. Education about waste must be instilled from an early age. The minimize of interesting education for the community makes moral messages about waste less noticeable by the public.The purpose of this study was to determine the effect of the STOP TRASH snake and ladder game media in increasing knowledge and attitudes towards waste on students in Indramayu.This research type is quasi experimental with pretest and posttest design. population was all students of SDN Singaraja and Singajaya class IV s.d. VI. The sample of 207 students. This study uses the Wilcoxon test. Knowledge with Result Z = -5.146b A-symp. Sig (2-tailed) 0.000. Attitude with result Z = -6.604b A-symp. Sig (2-tailed) 0.000.The results of this study can be concluded that there is a significant influence of the "stop trash" game media on increasing the knowledge and attitudes of students. Game media has advantages including providing a fun and helping to improve communicative and cognitive abilities. Game media is the right media to increasing students' knowledge and attitudes in managing waste and being responsible for the waste generated.